Leucocyte function in Crohn's disease. Studies on mobilisation using a quantitative skin window technique and on the function of circulating polymorphonuclear leucocytes in vitro. Issue 3 (March 1982) - Wandall, J H; Binder, V
Abstract : Leucocyte function was evaluated by mobilisation to skin windows with chambers and by the chemotactic, phagocytic, and nitro blue tetrazolium (NBT) reducing activity of circulating leucocytes in vitro in 20 patients with Crohn's disease, 21 healthy volunteers, and nine patients with sarcoidosis or tuberculosis. Leucocytes had been mobilised in significantly reduced numbers at 12, 24, 36, and 48 hours in Crohn's disease compared with healthy volunteers (P less than 0.01) and patients with sarcoidosis/tuberculosis (P less than 0.01). The leucocyte migration rate showed that mobilisation in Crohn's disease begins after a prolonged lag phase and is reduced compared with healthy volunteers (P less than 0.01) and patients with sarcoidosis/tuberculosis (P less than 0.02). The reduced mobilisation was not correlated with disease activity. In vitro random migration by leucocytes was slightly lower in Crohn's disease (P less than 0.05) than in healthy volunteers, but there was no difference after removal of the autologous plasma. Chemotactic response to casein did not differ between the groups studied. Serum independent and dependent phagocytosis did not differ from control groups. Serum independent phagocytosis was positively and significantly correlated to the disease activity (rho 0.4812, P less than 0.05). Resting leucocyte NBT reduction was increased in Crohn's disease and sarcoidosis/tuberculosis (P less than 0.01), but during phagocytosis a lower NBT reduction was found in Crohn's disease than in healthy volunteers (P less than 0.02). The inflammatory response in Crohn's disease, with reduced leucocyte accumulation, differs from patients with other granulomatous reactions and is independent of the disease activity. Our data suggest that the defect is not cellular. They support the hypothesis that a pathogenic factor in Crohn's disease may be foreign material that is normally eliminated remaining in the tissue and eliciting a chronic inflammatory response.